Age-Modulated Associations between KIBRA, Brain Volume, and Verbal Memory among Healthy Older Adults - Stickel, Ariana; Kawa, Kevin; Walther, Katrin; Glisky, Elizabeth; Richholt, Ryan; Huentelman, Matt; Ryan, Lee (Frontiers in Aging Neuroscience, 2018)
The resource modulation hypothesis suggests that the influence of genes on cognitive functioning increases with age. The KIBRA single nucleotide polymorphism rs17070145, associated with episodic memory and working memory, has been suggested to follow such a pattern, but few studies have tested this assertion directly. The present study investigated the relationship between KIBRA alleles (T carriers vs. CC homozygotes), cognitive performance, and brain volumes in three groups of cognitively healthy adults —middle aged (ages 52 - 64, n = 38), young old (ages 65 - 72, n = 45), and older old (ages 73 - 92, n = 62) – who were carefully matched on potentially confounding variables including apolipoprotein ε4 status and hypertension. Consistent with our prediction, T carriers maintained verbal memory performance with increasing age while CC homozygotes declined. Voxel-based morphometric analysis of magnetic resonance images showed an advantage for T carriers in frontal white matter volume that increased with age. Focusing on the older old group, this advantage for T carriers was also evident in left lingual gyrus gray matter and several additional frontal white matter regions. Contrary to expectations, neither KIBRA nor the interaction between KIBRA and age predicted hippocampal volumes. None of the brain regions investigated showed a CC homozygote advantage. Taken together, these data suggest that KIBRA results in decreased verbal memory performance and lower brain volumes in CC homozygotes compared to T carriers, particularly among the oldest old, consistent with the resource modulation hypothesis.